GIS, remote sensing and cartography for mapping and managing quarries and mines in Cyprus - Hadjimitsis, Diofantos G.; Themistocleous, Kyriacos; Onoufriou, Toula (My University, 2008)
Integration of remote sensing, geographic information system (GIS) and cartography can provide a means to find and update information about the location of quarries and mines, type of quarrying material, quarrying zone and mapping data in the Cyprus area for better management and planning. Indeed, the authors provide a description of their proposed methodology which is based on the integration of field data, satellite remotely sensed data, GIS platform and system, auxiliary data such as cadastral maps and sheets. Such tools have been used to develop the proposed system which gives the following information
Keywords: Remote Sensing; Cartography; map